Wolbert G.C. Smidt, Photos as Historical Witnesses: The First Ethiopians in Germany and the First Germans in Ethiopia, the History of a Complex Relationship. With an Introduction by Richard Pankhurst - Braukämper, Ulrich (Aethiopica, 2017)
Review